Countermovement jump performance is related to start and turn performance in young competitive swimmers - Forsyth, J. R.; Steele, J. R. (Journal of Australian Strength and Conditioning, 2019)
The ability of young competitive swimmers to produce explosive lower body force is related to track start and tumble turn performance during the 100 m freestyle, and practitioners should emphasise the development of these qualities leading into competition.